MATHEMATICS TEACHERS’ PERCEPTION ABOUT STEM-BASED LEARNING - Fitri Aida Sari; Dadang Juandi (FKIP Universitas Muhammadiyah Tangerang, 2021)
STEM has long been developed to produce a generation who is ready to face the challenges of the future era. STEM combines four elements (Science, Technology, Engineering, and Mathematics) in a learning process to make it more meaningful. STEM has been widely applied in developed countries, but in Indonesia, it has received less attention and has not been implemented in the education curriculum. The purpose of this study is to describe teachers' perceptions about the application of STEM, whether it is suitable to be applied in each school where the teacher works, what facilities are needed, and whether it is suitable to be applied during the pandemic Covid-19. This research method used a qualitative descriptive method by distributing open questionnaires to mathematics teachers from various regions. The results showed that most teachers agreed to use STEM in learning mathematics, including its application during the pandemic Covid-19. Besides, many things must be prepared before it can be applied, including the readiness and understanding of teachers regarding STEM, the availability of STEM teaching materials, and the availability of supporting facilities for each student and their ability to use them.